Analysis of Nickel Ore Content Results of the Blending Methode at PT. Aneka Tambang Tbk Site Pakal, East Halmahera Regency - Rita Purnama Sari; Arbi Haya; Firman Firman; Almun Madi; Alifianty Delila Imani (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
There is a variation in nickel content produced by PT. Aneka Tambang Tbk Site Pakal with the needs of the processing industry so that the blending method needs to be applied. Blending is the process of mixing two or more materials that have different qualities to get the right mixture. In the blending process, it must meet the specific ore according to the needs of the processing plant. The results of the XRF analysis on the stockpile Sosolat, Bicoli, Maba, Mafia, Sangaji, Roomstock Harmony, Resampling Sangaji were respectively 2.26%, 1.61%, 1.48%, 1.35%, 1.32%, 1.53%, and 1.60%. The results of theoretical simulations and actual blending in the field obtained factory quality of 1.75%, Buana Jaya barge with simulated Ni content of 1.87% and realized Ni content of 1.76%, Bukit Emas barge with simulated Ni content of 1.83% and realized Ni content of 1.90, TGH barge with simulated Ni content of 1.85% and realized Ni content of 1.76%, Ilir Jaya barge with simulated Ni content of 1.87% and real Ni content sai is 1.85%, the DBS 3029 barge with a simulated Ni content of 1.88% and a realized Ni content of 1.78%.